Removal of Cd (II) ions from Aqueous Solution by Adsorption on Activated Carbon Prepared from Lapsi (Choerospondias axillaris) Seed Stone - Shrestha, Rajeshwar Man (Journal of the Institute of Engineering, 2016)
Batch adsorption experiments were conducted for the adsorption of Cd (II) ions from aqueous solution by activated carbon prepared from Lapsi seed stone. The activated carbon was characterized by Iodine number, Methylene blue number, SEM and FTIR. Adsorption experiments were carried out to describe the effect of pH ,contact time and adsorbent dose on the metal ion removal process .The results showed that the adsorption of Cd (II) ions was very fast initially and the equilibrium time was 3 hrs.The pH of 6.0 was an optimal pH for adsorption of Cd(II) ions. Langmuir and Freundlich adsorption isotherms were used to explain the equilibrium data. Langmuir model best described the data with higher value of coeffcient of determination as −1 compared to that of Freundlich isotherm showing a maximum uptake of 37.0 mgg . This study demonstrated that the activated carbons prepared from Lapsi seed stone could be used for the removal of Cd (II) ions in water treatment. Journal of the Institute of Engineering, 2015, 11(1): 140-150